Sociodemographic and Lifestyle Factors Associated with Adherence to Mediterranean Diet in Representative Adult Population in Casablanca City, Morocco: A Cross-Sectional Study - Karima Mohtadi; Rajaa Msaad; Najwa Benalioua; Ali Jafri; Hasnaa Meftah; Younes Elkardi; Halima Lebrazi; Anass Kettani; Abdelfettah Derouiche; Hassan Taki; Rachid Saïle (Journal of Nutrition and Metabolism)
Several studies had revealed that following the Mediterranean diet (MD) contributes to beneficial health status and a decreased risk of many chronic diseases. The aim of our study was to assess adherence to MD in Casablanca City and to identify the relationship between MD adherence and sociodemographic and lifestyle parameters. This cross-sectional study concerned 719 subjects with complete dietary data. Data collection was performed using a questionnaire including sociodemographic and lifestyle factors. The dietary intake was assessed with the use of a food-frequency questionnaire. The compliance with MD was evaluated with a simplified MD score. Our study showed that high adherence to the MD was characterized by high intakes of vegetables, fruits, pulses, fish, cereals, olive oil, and low meat and dairy consumption according to the Simplified MD score. As regard to the multivariate logistic, being a man, being married, persons with a level of education >6 years, luxurious housing, and consumption of alcohol were associated with a higher adherence to MD, while, the overweight was negatively associated with a higher adherence to MD. Maintaining the traditional MD pattern is crucial for public health; in this way, more research is needed in this area in order to precisely measure these associations.